Experimental evidence of a functional relationship within the brainstem trigeminocervical complex in humans - Basedau, Hauke; Nielsen, Trine; Asmussen, Katharina; Gloss, Katrin; Mehnert, Jan; Jensen, Rigmor H.; May, Arne (Pain (Amsterdam), 2022)
The existence of a trigeminocervical complex has been suggested based on animal data, but only indirect evidence exists in humans. We investigated the functional relationship between the trigeminal and the occipital region by stimulating one region and measuring electrical pain thresholds (EPTs) of the corresponding opposite region. This study consists of 2 single-blinded, randomised protocols. Forty healthy participants were recruited in the propaedeutic protocol I. Electrical pain thresholds were measured on the V1 and the greater occipital nerve (GON) dermatome bilaterally as well as on the left forearm longitudinally before and after application of topical capsaicin. Protocol II was then online preregistered, and, additionally, the ipsilateral trigeminal dermatomes V2 and V3 were tested. Greater occipital nerve stimulation increased the EPT ipsilateral at V1 after 20 minutes ( P = 0.006) compared with baseline, whereas trigeminal stimulation increased the EPT at the ipsilateral ( P = 0.023) as well as the contralateral GON ( P = 0.001) after capsaicin application. Protocol II confirmed these results and additionally showed that GON stimulation with capsaicin increased EPTs ipsilateral at all 3 trigeminal dermatomes and that trigeminal stimulation on V1 led to an ipsilateral increase of EPTs at GON, V2, and V3. Our data suggest a strong functional interplay between the trigeminal and occipital system in humans. The fact that the stimulation of one of these dermatomes increases the EPT of the respective other nerve could be explained by segmental inhibition on the brainstem level.